Systematic Review: Side Efffects of Ramipril and Spironolactone Drug Combination in Cardiovascular Patients - Fadhilah Nurul Hayati; Lantip Rujito (Indonesian Journal of Global Health Research, 2025)
Cardiovascular disease is one of the leading causes of death worldwide, especially in developing countries. Combination therapy of ramipril, an ACE inhibitor, and spironolactone, an aldosterone antagonist, is widely used in hypertension and heart failure patients, offering clinical benefits such as blood pressure control and organ protection, but it also poses risks of hyperkalemia and renal dysfunction. This systematic review aimed to evaluate and identify the adverse effects of ramipril–spironolactone combination therapy. A systematic search was conducted in Google Scholar and PubMed NIH Central for articles published between 2020–2024 using the keywords “Ramipril” AND “Spironolactone” AND “Adverse Effect” and “Combination Therapy” AND “Cardiovascular Disease.” From an initial 1,026 articles, 38 were screened, 37 remained after duplicate removal, and 3 studies (2 from Google Scholar and 1 from PubMed) met the inclusion criteria. Article selection followed PRISMA 2020 guidelines, and data were extracted on study design, population, interventions, outcomes, and adverse effects. The results indicate that although ramipril–spironolactone combination therapy provides significant cardiovascular benefits, it is consistently associated with hyperkalemia, hypotension, and renal dysfunction; therefore, close monitoring of potassium levels, renal function, and blood pressure is strongly recommended to minimize adverse outcomes.